Genetic Diversity Among Old Local Grape Cultivars in South of Syria - M. Muzher, Bayan; T. Al-Halabi, Ola (International Journal of Environment, 2019)
This investigation was carried out in Sweida governorate of Syria from 2014 to 2015. The purpose of this investigation was to estimate the genetic diversity among 17 old local grape cultivars using morphological traits and SSR molecular markers. Principal Component Analysis (PCA) of morphological traits revealed that four main components were accountable for 50.34 % of variance, with Eigen values of 16.77%, 13.31%, 10.59% and 9.67%, respectively. While distribution of cultivars was found significantly dependent of first and second components, which separated Aswad Sharar and Derbly cultivars rather than other studied cultivars. Hierarchical cluster of morphological traits showed high diversity among studied cultivars. On the other hand, molecular characterization was conducted using eight informative SSR primer pairs, polymorphism was detected by seven SSR’s primers. As a result, 18 polymorphic alleles were revealed with a polymorphism percentage of 100%, which reflected the genetic variation among studied cultivars. Genetic similarity was achieved, where 0.875 was the highest between Zeiny and Khedry cultivars, while the other two cultivars Ebeidy and AhmarMokamaa showed the lowest genetic similarity as 0.077. Cluster analysis of SSR markers grouped the studied cultivars into three clusters as per Jaccard coefficient. The first cluster grouped Ebeidy, Aswad Helwany and Derbly cultivars together, the second cluster contained two cultivars Beiady and Alb Atair, while the third cluster contained the remaining cultivars. Consequently, the results showed high diversity among studied cultivars, and some morphological traits were useful for cultivar discrimination.